Corpus Académie française (ORTOLANG)
Le Corpus Académie française est un corpus lemmatisé et étiqueté des textes publiés sur le site de l'Académie française dans les rubriques « Discours », « Dire, ne pas dire » et « Questions de langue. 1635 à nos jours.
Keywords: _open access

African American Women Writers of the 19th Century - Divisions, Schomburg Center Research (NYPL)
African American Women Writers of the 19th Century guide includes a digital collection of published works by 19th-century black women writers, biographies for each author, citations and much more
Keywords: _100+; _open access